2021
DOI: 10.3389/fmed.2021.583086
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Dosage Individualization of Suppressive Beta-Lactam Therapy Administered by Subcutaneous Route in Patients With Prosthetic Joint Infection

Abstract: Suppressive parenteral antibiotic therapy with beta-lactams may be necessary in patients with Gram-negative bone and joint infection (BJI). Subcutaneous drug administration can facilitate this therapy in outpatient setting, but there is limited information about this practice. We have developed an original approach for drug dosing in this context, based on therapeutic drug monitoring (TDM) and pharmacokinetic/pharmacodynamic (PK/PD) principles. The objective of this study was to describe our approach and its f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…This problem is minimized in animal infection model or dynamic in vitro infection model studies aimed at elucidating the predictive PK-PD index and target values for various magnitudes of bacterial kill by ensuring that several bacterial strains are included in the study to inform setting of PK-PD targets and breakpoints (Zhao et al, 2016;Mouton et al, 2018b;Jorda and Zeitlinger, 2020). However, an inaccurate estimate from a single determination of MIC for an isolate from a particular patient is problematic in the clinical application of MIC-based PK-PD targets within the framework of what has been described as therapeutic drug monitoring (TDM) (Mouton et al, 2018b;Roberts et al, 2019;Märtson et al, 2020;Seeger et al, 2021a;Goutelle et al, 2021;Jorgensen et al, 2021;Moser et al, 2021). Thus, if an isolate from an infected patient returns an MIC estimate from an assay which has a typical error range of two dilutions (i.e., potentially a 4-fold range of reported MIC values), it follows that the PK-PD driven target plasma concentration for that patient would vary 4-fold if the PK-PD index for the antibiotic is fAUC/MIC or fC max /MIC.…”
Section: Mic: a Highly Problematic Measure Of Antibacterial Pd Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is minimized in animal infection model or dynamic in vitro infection model studies aimed at elucidating the predictive PK-PD index and target values for various magnitudes of bacterial kill by ensuring that several bacterial strains are included in the study to inform setting of PK-PD targets and breakpoints (Zhao et al, 2016;Mouton et al, 2018b;Jorda and Zeitlinger, 2020). However, an inaccurate estimate from a single determination of MIC for an isolate from a particular patient is problematic in the clinical application of MIC-based PK-PD targets within the framework of what has been described as therapeutic drug monitoring (TDM) (Mouton et al, 2018b;Roberts et al, 2019;Märtson et al, 2020;Seeger et al, 2021a;Goutelle et al, 2021;Jorgensen et al, 2021;Moser et al, 2021). Thus, if an isolate from an infected patient returns an MIC estimate from an assay which has a typical error range of two dilutions (i.e., potentially a 4-fold range of reported MIC values), it follows that the PK-PD driven target plasma concentration for that patient would vary 4-fold if the PK-PD index for the antibiotic is fAUC/MIC or fC max /MIC.…”
Section: Mic: a Highly Problematic Measure Of Antibacterial Pd Activitymentioning
confidence: 99%
“…Clearly, if the "true" MIC of the isolate is at the top of the error range but the reported MIC is at the bottom of the range, there is substantial risk of under dosing the patient. If the converse applied for an antibiotic of low therapeutic index, there may be increased risk of treatment-related toxicity if the reported MIC resulted in the decision to increase the dosage regimen (Märtson et al, 2020;Goutelle et al, 2021). Either of these outcomes may decrease the probability of achieving a good clinical outcome for the patient.…”
Section: Mic: a Highly Problematic Measure Of Antibacterial Pd Activitymentioning
confidence: 99%
“…The included studies are summarised in Table S3 [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Best practice for carbapenem TDM is not known, which has led to differences in the way it is carried out, particularly concerning pharmacological targets, dose-adjustment protocols, and frequency of antibiotic concentration measurement.…”
Section: Resultsmentioning
confidence: 99%
“…The prolonged t 1/2 associated with the s.c. administration of beta-lactams and the potential for patient self-medication make this route of administration very attractive, especially for infections requiring long-term antibiotic therapy, such as prosthetic joint infections. In our review, we included two case series describing the use of beta-lactams (ceftriaxone, ceftazidime, ertapenem) administered via the s.c. route for the treatment of chronic osteoarticular infections [11,14]. The s.c. administration of beta-lactams could be particularly useful for the treatment of chronic infections caused by Gram-negative bacteria, which are difficult to treat without inducing susceptibility to oral antibiotics, a very common situation in countries where MDR Gram-negative bacteria are frequently isolated.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the issue was the lack of knowledge regarding the ertapenem minimum inhibitory concentration (MIC) for E. cloacae at the onset of treatment. Subsequently, it was discovered that the MIC value was 0.38 mg/L, and the PK profile revealed that the thrice-weekly regimen did not achieve a sufficient fraction of time above the MIC (fT > MIC) [14].…”
Section: Carbapenemsmentioning
confidence: 99%